MUSASHI‐2 confers resistance to third‐generation EGFR‐tyrosine kinase inhibitor osimertinib in lung adenocarcinoma. Issue 9 (13th July 2021) - Yiming, Reheman; Takeuchi, Yasuto; Nishimura, Tatsunori; Li, Mengjiao; Wang, Yuming; Meguro‐Horike, Makiko; Kohno, Takashi; Horike, Shin‐ichi; Nakata, Asuka; Gotoh, Noriko
Abstract: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) are effective in patients with non–small‐cell lung cancer (NSCLC) harboring EGFR mutations. However,  due to acquired resistance to EGFR‐TKIs, even patients on third‐generation osimertinib have a poor prognosis. Resistance mechanisms are still not fully understood. Here, we demonstrate that the increased expression of MUSASHI‐2 (MSI2), an RNA‐binding protein, is a novel mechanism for resistance to EGFR‐TKIs. We found that after a long‐term exposure to gefitinib, the first‐generation EGFR‐TKI lung cancer cells harboring the EGFR‐TKI‐sensitive mutations became resistant to both gefitinib and osimertinib. Although other mutations in EGFR were not found, expression levels of Nanog, a stemness core protein, and activities of aldehyde dehydrogenase (ALDH) were increased, suggesting that cancer stem‐like properties were increased. Transcriptome analysis revealed that MSI2 was among the stemness‐related genes highly upregulated in EGFR‐TKI‐resistant cells. Knockdown of MSI2 reduced cancer stem‐like properties, including the expression levels of Nanog, a core stemness factor. We demonstrated that knockdown of MSI2 restored sensitivity to osimertinib or gefitinib in EGFR‐TKI‐resistant cells to levels similar to those of parental cells in vitro. An RNA immunoprecipitation (RIP) assay revealed that antibodies against MSI2 were bound to Nanog mRNA, suggesting that MSI2 increases Nanog expression by binding to Nanog mRNA. Moreover, overexpression of MSI2 or Nanog conferred resistance to osimertinib or gefitinib in parental cells. Finally, MSI2 knockdown greatly increased the sensitivity to osimertinib in vivo. Collectively, our findings provide proof of principle that targeting the MSI2‐Nanog axis in combination with EGFR‐TKIs would effectively prevent the emergence of acquired resistance. Abstract : Osimertinib (AZD9291) is a third‐generation irreversible, oral EGFR‐TKI that is effective without serious adverse effects, however, similar to earlier generations of EGFR‐TKIs, acquired resistance to osimertinib remains a major challenge. We discovered MSI2 as a novel target to overcome resistance to EGFR‐TKIs including osimertinib. Mechanistically, we demonstrate that MSI2 confers cancer stem‐like properties in lung adenocarcinoma cells, leading to resistance to the EGFR‐TKIs.